Early Trauma and Later Sexual Victimization in College Women: A Multiple Mediation Examination of Alexithymia, Impulsivity, and Alcohol Use. Issue 19 (October 2022) - Mullet, Natira; Hawkins, Lindsey G.; Tuliao, Antover P.; Snyder, Hailey; Holyoak, Derek; McGuire, Kimberly C.; Earl, Alicia K.; McChargue, Dennis
Childhood abuse and sexual violence against women are prevalent in the United States. However, researchers have not fully explored the intersection among important predisposing factors that predict recent sexual violence experienced by women who are also survivors of childhood abuse. The purpose of this study was to examine the relationships among early childhood trauma, alexithymia, impulsivity, alcohol use severity, and sexual victimization in later life among female college students from the United States ( n = 1, 178). Participants were part of a larger cross-cultural study, conducted between 2012 to 2014, which examined sexual aggression and victimization in the context of alcohol use. The current study aimed to examine if: (a) early trauma, impulsivity, alexithymia, and alcohol use severity impact sexual victimization in later life, and (b) if impulsivity, alexithymia, and alcohol use severity mediate the relationship between early trauma and victimization in later life. It was hypothesized that impulsivity, alexithymia, and alcohol use severity would significantly mediate the relationship between early trauma and sexual victimization in later life. Using a multiple mediation path analysis, results indicated that early childhood trauma was significantly linked with impulsivity, alcohol use severity, and sexual victimization in later life. A partial mediation through impulsivity and alcohol use severity was observed. Alexithymia did not produce mediation effects. These findings align with previous research examining how early childhood trauma influences the occurrence of sexual victimization in later life and provides further recommendations for helping professionals as they attempt to stifle the sexual victimization rates among female college students.